Penerapan pengendalian kualitas pada lantai produksi PT. Adi Satria Abadi Jl.Laksda Adi Sucipto KM 11 Sidokerto Rt.03/ Rw.01 Purwomartani, Kalasan, Sleman, Yogyakarta - Ibni Hanafi (Fak. Sains dan Teknologi UIN Sunan Kalijaga, 2013)
ngdm/nr,c.1